Relationship between acetaldehyde concentration in mouth air and tongue coating volume - Aya YOKOI; Takayuki MARUYAMA; Reiko YAMANAKA; Daisuke EKUNI; Takaaki TOMOFUJI; Haruhiko KASHIWAZAKI; Yutaka YAMAZAKI; Manabu MORITA (Journal of Applied Oral Science, 2015)
Objective Acetaldehyde is the first metabolite of ethanol and is produced in the epithelium by mucosal ALDH, while higher levels are derived from microbial oxidation of ethanol by oral microflora such as Candida species. However, it is uncertain whether acetaldehyde concentration in human breath is related to oral condition or local production of acetaldehyde by oral microflora. The aim of this pilot study was to investigate the relationship between physiological acetaldehyde concentration and oral condition in healthy volunteers. Material and Methods Sixty-five volunteers (51 males and 14 females, aged from 20 to 87 years old) participated in the present study. Acetaldehyde concentration in mouth air was measured using a portable monitor. Oral examination, detection of oral Candida species and assessment of alcohol sensitivity were performed. Results Acetaldehyde concentration [median (25%, 75%)] in mouth air was 170.7 (73.5, 306.3) ppb. Acetaldehyde concentration in participants with a tongue coating status score of 3 was significantly higher than in those with a score of 1 (p<0.017). After removing tongue coating, acetaldehyde concentration decreased significantly (p<0.05). Acetaldehyde concentration was not correlated with other clinical parameters, presence of Candida species, smoking status or alcohol sensitivity. Conclusion Physiological acetaldehyde concentration in mouth air was associated with tongue coating volume.